The Chow Motives of Relative Fulton-Macpherson Space - Sato, Fumitoshi (MATHEMATICA SCANDINAVICA, 2013)
Suppose that X is a complex nonsingular projective variety and D is a smooth divisor. Compactifications of configuration spaces of distinct and non-distinct n points in X away from D were constructed by the author and B. Kim in "A generalization of Fulton-MacPherson configuration spaces" by using the method of wonderful compactification. In this paper, we give explicit presentations of Chow motives and Chow groups of these configuration spaces.